Launch the Intruders : A Naval Attack Squadron in the Vietnam War, 1972 - Reardon, Carol (Book collections on Project MUSE., 2018)
A true Band of Brothers story from the Vietnam War, this first unit history of a naval air squadron uses extensive interviews to highlight the Navy's contribution to the air war.